Peningkatan Kemampuan Menulis Teks Pidato dengan Menggunakan Metode Think Fair Share - Gagan Zakaria (Universitas Suryakanca, 2017)
This article discusses improving the ability to write speech text by using think fair share method. The study was conducted using Classroom Action Research (PTK) with two cycles. Technique of collecting data is done by test. The results showed that there was an increase in the ability to write speech texts and student activities. This can be seen in the cycle I the ability to write speech text with completeness reached 60.68% or 70 average. Then it looks a significant increase compared to cycle I, in cycle II mastery reaches 91.30% or an average of 82.34. Furthermore, students' activity in cycle I was recorded by 4 students or 17.39% who played mobile phone, 3 students or 13.04% who were relaxed waiting for the reply from their friends, and 2 students or 8.69% who cheered his friend when doing. Compared to cycle I, some students do not want to do themselves according to the instructions. In the implementation of cycle II, the activity of students who play mobile phone decreased from 4 students or by 17.39% to 2 students or by 8.69%, relaxed students waiting for answers from their friends no, and students who bully his friend does not exist.Keywords: writing text of speech, think fair share.